1998
DOI: 10.3109/10826089809059340
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Gambling and Substance Misuse: A Review of the Literature

Abstract: This paper reviews research conducted on the link between pathological gambling and substance misuse. We first examine the phenomenon of "pathological gambling," including similarities between pathological gambling and substance misuse, instruments used to measure pathological gambling, and the prevalence of pathological gambling in the United States and internationally. We then examine research on substance misuse among pathological gamblers, pathological gambling among substance misusers, and the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 42 publications
4
38
0
7
Order By: Relevance
“…Furthermore, several studies have shown higher rates of pathological gambling among drug addicts (cf. Cunningham-Williams, Cottler, Compton, Spitznagel & Ben-Abdallah, 2000;Langenbucher, Bavly, Lavouvie, Sanjuan & Martin, 2001;Orford et al, 2003;Spunt, Dupont, Lesieur, Liberty & Hunt, 1998;Steinberg, Kosten & Rounsaville, 1992;Toneatto & Brennan, 2002;Toneatto, Ferguson & Brennan, 2003;Villas, Collakis, Magalhäes & da Silveira, 2005), and have demonstrated its influence on therapeutic results (Ledgerwood & Downey, 2002). Moreover, several studies with methadone patients have found rates of current pathological gambling ranging from 7% to 18% (Feigelman, Kleinman, Lesieur, Millman & Lesser, 1995;Ledgerwood & Downey, 2002;Spunt, Lesieur, Liberty & Hunt, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have shown higher rates of pathological gambling among drug addicts (cf. Cunningham-Williams, Cottler, Compton, Spitznagel & Ben-Abdallah, 2000;Langenbucher, Bavly, Lavouvie, Sanjuan & Martin, 2001;Orford et al, 2003;Spunt, Dupont, Lesieur, Liberty & Hunt, 1998;Steinberg, Kosten & Rounsaville, 1992;Toneatto & Brennan, 2002;Toneatto, Ferguson & Brennan, 2003;Villas, Collakis, Magalhäes & da Silveira, 2005), and have demonstrated its influence on therapeutic results (Ledgerwood & Downey, 2002). Moreover, several studies with methadone patients have found rates of current pathological gambling ranging from 7% to 18% (Feigelman, Kleinman, Lesieur, Millman & Lesser, 1995;Ledgerwood & Downey, 2002;Spunt, Lesieur, Liberty & Hunt, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…the type of game (the quicker the bet-to-pay interval, the higher the frequency and the risk), the initial gain (a high win leads to problem gambling), and the tools and context (for example, the anonymity and lack of social contact in online gaming are considered risk factors), as well as the offer and availability of games. Comorbid disorders such as alcohol and drug abuse (Spunt et al 1998) also play a role in increasing extreme gambling behaviour. The second group includes environmental and context factors, ranging from cultural and religious (influence of obligations, religious restrictions) to economic and socio-educational ones (parents and family context, socio-economic status).…”
Section: Gambling and Masculinitymentioning
confidence: 99%
“…A big rise in PG has been recorded among substance abusers. PG has been linked to a history of child hood experiences of gambling in the family, high rates of stress problems and serious psychiatric conditions [20,21].…”
Section: Epidemiology Of Pathological Gamblingmentioning
confidence: 99%